2017
DOI: 10.1016/j.medici.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction in patients with acute kidney injury requiring renal replacement therapy after cardiac surgery

Abstract: Our study demonstrated that SOFA score estimation is the most accurate to predict the fatal outcome in patients with AKI requiring RRT after cardiac surgery. Lethal patient outcome is related to Glasgow coma score, mean arterial blood pressure, preoperative serum creatinine and postoperative platelet count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…When we compared the ventilated non-AKI participants to the ventilated AKI participants, the ventilated AKI participants had a higher APACHE score and three days SOFA score. This finding confirmed that AKI in ICU is a prominent risk factor that can worsen the patients' health conditions, more specifically in low-risk AKI-RRT patients [22]. In addition, Vieira, et al, showed that renal dysfunction had a serious consequence during the use of mechanical ventilation and weaning from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…When we compared the ventilated non-AKI participants to the ventilated AKI participants, the ventilated AKI participants had a higher APACHE score and three days SOFA score. This finding confirmed that AKI in ICU is a prominent risk factor that can worsen the patients' health conditions, more specifically in low-risk AKI-RRT patients [22]. In addition, Vieira, et al, showed that renal dysfunction had a serious consequence during the use of mechanical ventilation and weaning from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 58%
“…In order to reach the acceptable gas exchange level, therefore mechanical ventilation is needed to increase the intrathoracic pressure to compensate for these negative changes. If mechanical ventilation is not used, then the AKI patients can progress to renal dysfunction such as renal tubular apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports concerning blood pressure related to mortality among AKI requiring RRT [17,31], and instead of renal prognosis, some reports disclose better prognosis with higher MAP among AKI. Among patients with postgastrointestinal surgery, the MAP comparing 80-95 mmHg with 65-79 mmHg is reported to have less incidence of AKI [38], and among patients with AKI requiring RRT after cardiac surgery, the lower MAP is associated with poor mortality [39]. As our results showed, the higher MAP would not be optimal rather than sole target of MAP ≥ 65 mmHg.…”
Section: Discussionmentioning
confidence: 59%
“…This will eventually result in renal dysfunction such as renal tubular apoptosis. (22) There are 92 patients (24.6%) AKI patients required RRT(AKI-RRT), this result might validate the importance of RRT in ICU settings, despite certain challenges such as availability of modalities and understaffing of nephrologist. (24) It is important to remember that AKI is a case with a staggering amount of mortality rates, especially for critically ill patients in ICU setting.…”
Section: Discussionmentioning
confidence: 82%
“…This study result might support current view that AKI in ICU is a prominent risk factor contributes to the worsening of patients' health conditions, more specifically in low-risk AKI-RRT patients. (22) Based on the study conducted by Vieira, et al shows that renal dysfunction has serious consequence in the duration of mechanical ventilation and weaning from mechanical ventilation. The median duration of mechanical ventilation use in AKI patients was 3 days longer than non-AKI patients (10 vs 7 days).…”
Section: Discussionmentioning
confidence: 99%